Trinidad and Tobago - Youth and Social Development : An Integrated Approach for Social Inclusion - World Bank (Washington, DC, 2013)
Trinidad and Tobago has experienced increasing social problems relating to its youth population despite the economy's improved performance. The report aims to uncover and analyze key issues facing the youths, explore a rationale for investing in youth development activities, review current services for youth, examine the existing and proposed policy and legislation relating to youth and capacity for its implementation, and propose interventions to reduce the risks faced by youths and increase the potential for social and human capital development. This report highlights the two principal exclusionary factors that contribute to increasing conditions of risk for youth in Trinidad and Tobago: a) restricted access to the secondary education system, which leaves out one third of the school-aged population; and b) the high level of unemployment, which reaches 30 percent for the 15 - 19 cohort, compared to 14 percent for the rest of the population. In addition, poverty, reduced family care, and exposure to youth protective services and the judicial system pose developmental risks that may contribute to negative outcomes such as youth involvement in crime and drug culture, early sexual activity and pregnancy. The report demonstrates that investments in youth services will help reduce these existing barriers and bring substantial economic and social returns for the individual and for society.